Engineering Glucose-to-Glycerol Pathway in Klebsiella pneumoniae and Boosting 3-Hydroxypropionic Acid Production Through CRISPR Interference - Liu, Hexin; Zhao, Peng; Tian, Pingfang (Frontiers in Bioengineering and Biotechnology, 2022)
The recent decline of international biodiesel industry has led to decreased production and therefore increased price of glycerol which is a major byproduct of biodiesel but a substrate for production of 3-hydroxypropionic acid (3-HP). That is, glycerol as a feedstock has no advantage over glucose in price. Hence, we engineered glucose to glycerol pathway and improved 3-HP production by CRISPR interference (CRISPRi). To begin with, we cloned the genes encoding glycerol 3-phosphate dehydrogenase (gpd1) and glycerol 3-phosphatase (gpp2) from Saccharomyces cerevisiae, which jointly catalyze glucose into glycerol. The genes gpd1 and gpp2 were co-expressed in Klebsiella pneumoniae with dCas9 gene integrated in genome, and this recombinant strain produced 2 g/L glycerol in shake flask. To minimize the glucose consumption by competing pathways including EMP pathway, glycerol oxidation pathway, and byproducts pathways, we developed an CRISPRi system in above recombinant K. pneumoniae strain to inhibit the expression of glyceraldehyde-3-phosphate dehydrogenase gene (gapA) and 2,3-butanediol production gene (budA), resulting in a bi-functional strain harboring both glucose-to-glycerol pathway and CRISPRi system. Reverse transcription and quantitative PCR (RT-qPCR) results showed that this engineered CRISPRi system transcriptionally inhibited gapA and budA by 82% and 24%, respectively. In shake flask cultivation, this bi-functional strain produced 2.8 g/L glycerol using glucose as the carbon source, which was 46.6% increase compared to the strain without the engineered CRISPRi system. Moreover, this bi-functional strain produced 0.78 g/L 3-HP using glucose as the sole carbon source. In fed-batch cultivation, this bi-functional strain produced 1.77 g/L 3-HP. This study provides insights for co-utilization of distinct carbon sources.